Effect of spatial arrangement and structure of hierarchically patterned fibrous scaffolds generated by a femtosecond laser on cardiomyoblast behavior. Issue 6 (25th March 2018) - Jun, Indong; Kim, Kyeongsoo; Chung, Yong‐Woo; Shin, Hyeok Jun; Han, Hyung‐Seop; Edwards, James R.; Ok, Myoung‐Ryul; Kim, Yu‐Chan; Seok, Hyun‐Kwang; Shin, Heungsoo; Jeon, Hojeong
Abstract: Biological responses on biomaterials occur either on their surface or at the interface. Therefore, surface characterization is an essential step in the fabrication of ideal biomaterials for achieving effective control of the interaction between the material surface and the biological environment. Herein, we applied femtosecond laser ablation on electrospun fibrous scaffolds to fabricate various hierarchical patterns with a focus on the alignment of cells. We investigated the simultaneously stimulated response of cardiomyoblasts based on multiple topographical cues, including scales, oriented directions, and spatial arrangements, in the fibrous scaffolds. Our results demonstrated a synergistic effect on cell behaviors of one or more structural arrangements in a homogeneous orientation, whereas antagonistic effects were observed for cells arranged on a surface with heterogeneous directions. Taken together, these results indicate that our hierarchically patterned fibrous scaffolds may be useful tools for understanding the cellular behavior on fibrous scaffolds used to mimic an extracellular matrix‐like environment. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1732–1742, 2018.